2016
DOI: 10.1002/cncr.30411
|View full text |Cite|
|
Sign up to set email alerts
|

Results of a randomized, prospective clinical trial evaluating metronomic chemotherapy in nonmetastatic patients with high‐grade, operable osteosarcomas of the extremities: A report from the Latin American Group of Osteosarcoma Treatment

Abstract: According to the current follow-up, EFS with MAP plus MC is not statistically superior to EFS with MAP alone in patients with high-grade, resectable OSTs of the extremities. Cancer 2017;123:1003-10. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 35 publications
(76 reference statements)
0
65
0
1
Order By: Relevance
“…In addition, Pramanik et al compared MC and supportive care in progressive pediatric solid malignant tumors and found that median PFS and OS were similar in both groups with BS. Lastly, a recent study, investigating the efficacy of the addition of MC to standard chemotherapy versus standard chemotherapy alone in patients with nonmetastatic high‐grade operable osteosarcoma, demonstrated that the addition of MC with methotrexate and cyclophosphamide was not statistically superior to the standard treatment without MC (5‐year PFS = 61% vs 64%, P = 0.395; 5‐year OS = 76% vs 73%, P = 0.539). Our study is consistent with these findings, and we do not believe that this MC regimen should be used for refractory/relapsing osteosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pramanik et al compared MC and supportive care in progressive pediatric solid malignant tumors and found that median PFS and OS were similar in both groups with BS. Lastly, a recent study, investigating the efficacy of the addition of MC to standard chemotherapy versus standard chemotherapy alone in patients with nonmetastatic high‐grade operable osteosarcoma, demonstrated that the addition of MC with methotrexate and cyclophosphamide was not statistically superior to the standard treatment without MC (5‐year PFS = 61% vs 64%, P = 0.395; 5‐year OS = 76% vs 73%, P = 0.539). Our study is consistent with these findings, and we do not believe that this MC regimen should be used for refractory/relapsing osteosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Our own group published the first randomized controlled trial in relapsed refractory solid tumors, and showed that metronomic therapy was no better than placebo; however, subgroup analysis revealed that tumors other than bone sarcoma showed benefit for both progression‐free survival and overall survival (OS) with the use of metronomic therapy. Further, specific tumor‐related studies with metronomics showed that this form of treatment appears to work in neuroblastoma and RMS, but not so in osteosarcoma …”
Section: Clinical Usage In Pediatricsmentioning
confidence: 99%
“…A recent Phase II study of oral etoposide in 30 patients of R/R osteosarcoma gave modest results . However, a large randomized study using oral methotrexate and cyclophosphamide as a maintenance strategy after curative treatment of nonmetastatic osteosarcoma reported no difference in OS …”
Section: Experience In Individual Pediatric Malignanciesmentioning
confidence: 99%
See 2 more Smart Citations